Serum resistin levels, and other hormonal and biochemical parameters in patients with polycystic ovary syndrome (PCOS) - Shamam, Kamila H.; El – Yassin, Hedef D.; Al – Shammaa, Haider (Journal of the Faculty of Medicine Baghdad, 2009)
Background: Polycystic ovarian syndrome (PCOS) is one of the most common cause of anovulation during reproductive life.Resistin can increase ovarian androgen production by directly stimulating ovarian theca cell or indirectly by augmenting pancreatic – B cell production of insulin.Patients and Methods: Sixty patients with PCOS who were non diabetic and not taking any medicine for the last three months were involved in the study .Thirty normal fertile female serves as control group. Fasting blood samples were aspirated from all individuals from 3rd - 6th day of the menstrual cycle to measure resistin, insulin, glucose, LH, FSH, TT3, TT4, Prolactin , Total Testosterone and lipid profile, by ELISA and routine methods.Results: mean serum resistin concentration was increased in women with PCOS compared with the control group (Mean ±SD) (19.83 ± 6.101 vs 9.36 ± 2.17) ng/ml. Serum resistin concentration correlated positively with BMI, which is divided into two subgroups. The first with BMI < 25 kg/m2 and the second with BMI ≥25kg/m2 in both control and patient groups. In BMI < 25kg/m2 serum resistin concentration for the control group was (8.90 ± 1.76) and (14.66 ± 2.09 ) for patients group ,while BMI ≥ 25 kg/m2 serum resistin concentration for the control group was (10.62 ± 1.76) and (21.55 ± 5.40) ng/ml for patients group. Resistin also correlated positively with Insulin, LH, LH/FSH ratio and total Testosteron in women with PCOS but not in control. Fasting insulin level was higher in PCOS group compared with the control group (Mean ±SD) (27.45 ± 4.47 vs 13.27 ± 3.80) mIU/ml.The Fasting serum glucose was also higher in PCOS group compared with the control group (Mean ±SD) (125.27 ± 28.63 vs 92.63 ± 13.99) mg/dl. Total Testosterone level was elevated in the PCOS group compared with the control group (1.04 ± 0.37 vs 0.52 ± 0.25) ng/ml.Total Testosterone correlated positively with BMI, Resistin, Insulin, LH, and LH/FSH ratio.Conclusion: PCOS women with BMI >25 kg/m² were found to have a marked increase level of Resistin ,Insulin , Glucose ,LH ,and Total Testosterone .and a decrease level in their insulinsensitivity i.e increased insulin resistance.These data indicate that abnormal resistin secretion in obese PCOS women may play a role in causing ovarian hyperandrogenism and hyperinsulinemia. Therefore fasting serum resistin level could be helpful in diagnosing PCOS patient.